"They are Assuming That We are Going to Accuse Them of Rape, and We are Assuming That They are Going to Rape us": A Developmental Perspective on Emerging Adults’ Consent Conversations Post #MeToo - Cary, Kyla M. (Journal of interpersonal violence, 2022)
Prevalence of sexual assault remains high on American college campuses, and sexual consent education is lacking within school-based sexual health education programming. Much empirical research has aimed to reduce sexual violence through a deeper understanding of college students? perceptions of sexual consent. However, researchers have not yet examined the impact of broader social discourse, such as that initiated by the #MeToo movement, on emerging adults? conceptualizations of sexual consent. Gendered focus groups were conducted with 34 college students at a large midwestern university in spring of 2019. Qualitative analyses using a phenomenological framework revealed a developmental process of consent education shaped by socialized sexual scripts and public discourse of the #MeToo movement. Four distinct themes emerged: (1) Introductions to Consent in Childhood, (2) Lack of Sexual Consent Education in Adolescence, (3) The Nuanced College Context, and (4) Consent in the Era of #MeToo. Findings reveal that consent is introduced in childhood, outside the context of sexuality, but is generally not revisited within the context of sexual consent by parents or educators during adolescence, leaving media messaging and socialized sexual scripts to serve as guides for sexual consent. This lack of sexual consent education in adolescence then leaves emerging adults unprepared for nuanced sexual experiences in the college context and unable to critically engage with public discourse surrounding consent such as the #MeToo movement, which has caused both fearful and positive outcomes. Findings support the need for earlier and more comprehensive education about sexual consent in childhood and adolescence and the need for college sexual assault prevention programs to include further instruction on navigating ambiguous sexual consent experiences.